2010
DOI: 10.1021/bm9014649
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Incorporation of Growth Factors in Decellularized Aortic Heart Valve Leaflets

Abstract: Aortic heart valve disease is a growing health problem and a tissue-engineered aortic heart valve could be a promising therapy. In this paper, decellularized porcine aortic heart valve leaflets are used as scaffolds and loaded with growth factor and heparin via layer-by-layer electrostatic deposition (LbL technique) with the final purpose to stimulate and control cellular processes. Binding and subsequent release of heparin and basic fibroblast growth factor (bFGF) from aortic valve leaflets were assessed qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…(1)], indicating that 50% of the peptide was released in the first 34 min. This release behavior is typical of protein that is allowed to diffuse freely once it is desorbed from a surface 15, 34. Release kinetics are mainly driven by the equilibrium partitioning between bound and free α‐MSH in solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)], indicating that 50% of the peptide was released in the first 34 min. This release behavior is typical of protein that is allowed to diffuse freely once it is desorbed from a surface 15, 34. Release kinetics are mainly driven by the equilibrium partitioning between bound and free α‐MSH in solution.…”
Section: Resultsmentioning
confidence: 99%
“…This release behavior is typical of protein that is allowed to diffuse freely once it is desorbed from a surface. 15,34 Release kinetics are mainly driven by the equilibrium partitioning between bound and free a-MSH in solution. Weaker interactions between loosely bound a-MSH, as well as the high concentration gradient at the start of the release experiment may contribute to the observed burst release.…”
Section: Release Of A-msh From Plga Microspheresmentioning
confidence: 99%
“…The sustained and control-released growth factor from such modified PEMs may be an alternative strategy to improve in situ stem cell adhesion, differentiation and growth. It was recently reported that bFGF could be loaded via layer-by-layer electrostatic deposition [20]. In present study, we used VEGF instead of bFGF because of its specificity to EPC [21].…”
Section: Discussionmentioning
confidence: 99%
“…32,47,48 Therefore, the pore size in the porous PLGA microspheres here should easily accommodate the formation of the multilayer films on the internal pore walls without significant pore blockage, consistent with our observations. Even without the addition of multilayer films, the low level burst release of a-MSH observed here was a significant improvement over previous studies using non porous microspheres where 60-80% of the loaded peptides (including a-MSH) or proteins was released within 2 h. 10,29,49 This is attributed to the pores in our system, which provide a more tortuous path for the peptide, reducing its release rate relative to unhindered diffusion from a nonporous surface. The small mass of a-MSH released in the initial burst is expected to result from a-MSH bound loosely on the surface or close to the external surface where pore tortuosity had little effect on diffusion.…”
Section: Discussionmentioning
confidence: 54%